Additive manufacturing of pure tungsten by means of selective laser beam melting with substrate preheating temperatures up to 1000 ∘C. (May 2019) - Müller, A. v.; Schlick, G.; Neu, R.; Anstätt, C.; Klimkait, T.; Lee, J.; Pascher, B.; Schmitt, M.; Seidel, C.
Highlights: Investigations regarding additive manufacturing of pure tungsten by means of selective laser beam melting are presented. Results for material fabricated with substrate preheating temperatures up to 1000 ∘ C are discussed. Examples of more complex additively manufactured thin-walled W structures that were also processed to composite material structures are presented. Abstract: The preferred plasma-facing material in present-day and future magnetic confinement thermonuclear fusion devices is tungsten. This material is mainly chosen because of its high threshold energy for sputtering by hydrogen isotopes as well as its low retention of tritium within the material. From an engineering point of view, however, tungsten is a challenging material to work with as it is an inherently hard and brittle metal. In this respect, established fabrication technologies for tungsten and tungsten based materials are a limiting factor directly affecting the design of plasma-facing components. Against this background, additive manufacturing technologies could prove very beneficial with regard to plasma-facing component applications as they offer flexibilities beyond the possibilities that conventional manufacturing methods offer. Within the present contribution, we report on recent results regarding the additive manufacturing of tungsten by means of powder-bed based selective laser beam melting. In more detail, investigations on pure tungsten manufactured by using elevated substrate preheating temperatures up to 1000  ∘ C are described.